Furnace Engine Modification to Lower Power - Catur Ahadi, Yeyen; Harmi Tjahjanti, Prantasi (Ann Publisher, 2023)
Furnace machine or heating furnace is a tool used for heat treatment processes or usually called heat treatment, furnace machines have several types from the beginning found furnace machines, namely induction furnaces/conventional furnaces and then transformed into electric furnaces, electric furnaces are more often used for processes heat treatment because it is cleaner compared to the convection furnace.The furnace machine requires 5000 watts of power, 13.1A. to reach the temperature of 8000 takes 7296 seconds. Furnace machine testing is by quenching using ST-42 steel which is held at 6000 and varying time, the first test material is not treated with heat traetment, for the second test material with a variation of 15 minutes, third 30, fourth 60, fifth 90, sixth 120 minute. the results of the quenching process were tested using the Brinell and Vickers hardness test methods.